2000
DOI: 10.1080/713661400
|View full text |Cite
|
Sign up to set email alerts
|

Mobile entrepreneurship: Informal sector cross-border trade and street trade in South Africa

Abstract: This article presents the results of a study on the participation of non-South Africans in the handicraft/curio sector of street trade in South Africa in informal sector cross-border trade. The findings provide an introduction to the largely unexplored phenomenon of informal sector cross-border trade between South Africa and neighbouring states and challenge some of the common myths about non-South African street traders which pervade public discourses around migration. The Southern African Development Communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 3 publications
(2 reference statements)
2
45
0
1
Order By: Relevance
“…According to Alusala (2010) and Mijere (2009), informal traders are often assumed to be poorly educated. However, the result of the research in Serikin is similar to the studies carried out by Peberdy (2000) and Peberdy & Crush (2001). It was found that 11.8% of the traders had obtained university education, 45.1% had an upper secondary school education, 11.8% had a lower secondary school education, 21.6% had a primary school education, and the remaining 7.8% had not attended school.…”
Section: Profile Of Cross-border Traderssupporting
confidence: 72%
See 2 more Smart Citations
“…According to Alusala (2010) and Mijere (2009), informal traders are often assumed to be poorly educated. However, the result of the research in Serikin is similar to the studies carried out by Peberdy (2000) and Peberdy & Crush (2001). It was found that 11.8% of the traders had obtained university education, 45.1% had an upper secondary school education, 11.8% had a lower secondary school education, 21.6% had a primary school education, and the remaining 7.8% had not attended school.…”
Section: Profile Of Cross-border Traderssupporting
confidence: 72%
“…It can be seen that cross-border trade stabilizes the market price of the goods supplied with the additional demand from the recipient country and provide job opportunities. However, in terms of tax collection, it is affected by the probability of not paying taxes, as mentioned by Ackello-Ogutu and Echessah (1998), Alusala (2010), Lesser andMoise-Leeman (2009), Macamo (1999), Peberdy (2000), Sikder, (2005 and Titeca & de Herdt (2010). The implication of cross-border trade also have spin-off activities, including human trafficking, smuggling of migrants, the spread of infectious diseases and crime as experienced in Laos, Combodia, Vietnam and Thailand (Paitoonpong, 2007) and at Uganda-Rwanda border (Alusala, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As demonstrated by a number of independent research investigations as well as a cluster of work linked to the Southern African Migration Project this form of informal business tourism is widespread between South Africa and other countries in southern Africa, most importantly Lesotho, Swaziland, Mozambique, Zimbabwe and Malawi (Muzvidziwa, 1998;Peberdy & Crush, 1998;Peberdy, 2000aPeberdy, , 2000bPeberdy & Crush, 2001;Peberdy & Rogerson, 2003;SBP, 2006;ComMark Trust, 2008;International Organization for Migration, 2010;Muzvidziwa, 2010;Chiliya, Masocha & Zindiye, 2012;Jamela, 2013). Johannesburg is host to a large circulating community of informal business travellers, mostly informal traders who cross South Africa's borders on a temporary basis to trade, shop and buy-and sell (Crush, 2005;Rogerson, 2011;Jamela, 2013).…”
Section: Conceptualizing Business Tourism In Africamentioning
confidence: 99%
“…Works by Peberdy and Crush (1998) and by Peberdy (2000aPeberdy ( , 2000bPeberdy ( , 2007 confirm that women entrepreneurs are most likely to be engaged in the more mobile segments of cross-border trade and selling, among other items, groceries, fresh food, clothing and craft goods. It is shown that communities of women traders operating in South Africa 'often travel to sell for only one week per month, and many sell direct to shops and customers and are more likely to be involved in cross-border "shopping" ' (Peberdy & Rogerson, 2000, p. 31).…”
Section: Informal Sector Business Tourism and Pro-poor Tourismmentioning
confidence: 99%